Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species - Ye, Zhen; Polhemus, Dan A.; Bu, Wenjun (Zootaxa, 2017)
Five species of the genus Amemboides Polhemus & Andersen are now known from China. Of these, A. pilifer (Zettel, Yang & Tran, 2007) and A. yunnanus (Zettel, Yang & Tran, 2007) were previously recorded from the country, while A. perlatus (Polhemus & Andersen, 1984) and A. vasarhelyii (Zettel, 1995) are newly recorded from China herein. In addition, A. fasciculatus sp. nov. is described from Yunnan Province. Photographs of the male and female dorsal habitus and male genitalic structures are provided for all five species of Amemboides known from China, and are accompanied by habitat photos and a distribution map.